UJI AKTIVITAS ANTIDIARE INFUSA KACANG PANJANG (Vigna sinensis L.) TERHADAP MENCIT PUTIH (Mus musculus) JANTAN - Inderiyani, Inderiyani; Herdaningsih, Sulastri; Pramana, Yoga; Olivia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Diarrhea is a disorder of defecation more than 3 times a day with a liquid stool consistency, which may be accompanied by blood and/or mucus. This plant has the potential to be used as an alternative treatment for diarrhea, one of which is cowpea (Vigna sinensis L.). Cowpea is a plant that has secondary metabolites in the form of flavonoids, sterols and tannins which are thought to have activity as antidiarrheal. This study aims to determine the activity and dose of cowpea as antidiarrheal against male white mice with oleum ricini-induced diarrhea protection. The test was carried out by inducing mice using 0,75 mL of Ricini oleum orally first, 1 hour later given a test solution in the form of 0,5% Na CMC suspension, 0,52 mg/kgBB loperamide test solution, cowpea infusa doses of 1,5 g/kgBB, 3 g/kgBB and 6 g/kgBB. Then observations were made on the weight of diarrhea feces and the diameter of water absorption every 30 minutes for 5 hours. The results showed that cowpea infusa with doses of 1,5 g/kgBB, 3 g/kgBB and 6 g/kgBB had activity as antidiarrheal indicated by a significant difference in the test group against the negative control group (p ≤0.05).